Electrical-field sensitive YBa?Cu?O??? detectors for real-time monitoring of picosecond THz pulses - Raasch, Juliane (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2019)
This work investigates the capability of the high-temperature superconductor YBCO to sense the evolution of the electrical field of THz pulses. A deposition process for ten unit-cell thin films and a sub-µm patterning process were developed to enable high sensitivities. The detector response to THz exctiations and its electrical-field sensitivity were studied. This unique characteristic allows for the investigation of instabilities of the THz radiation emitted from synchrotron storage rings.